The Degradation of Hyaluronan in the Skin - Žádníková, Petra; Šínová, Romana; Pavlík, Vojtěch; Šimek, Matěj; Šafránková, Barbora; Hermannová, Martina; Nešporová, Kristina; Velebný, Vladimír (Biomolecules, 2022)
Hyaluronan (HA) comprises a fundamental component of the extracellular matrix and participates in a variety of biological processes. Half of the total amount of HA in the human body is present in the skin. HA exhibits a dynamic turnover; its half-life in the skin is less than one day. Nevertheless, the specific participants in the catabolism of HA in the skin have not yet been described in detail, despite the essential role of HA in cutaneous biology. A deeper knowledge of the processes involved will act to support the development of HA-based topical and implantable materials and enhance the understanding of the various related pathological cutaneous conditions. This study aimed to characterize the distribution and activity of hyaluronidases and the other proteins involved in the degradation of HA in healthy human full-thickness skin, the epidermis and the dermis. Hyaluronidase activity was detected for the first time in healthy human skin. The degradation of HA occurred in lysates at an acidic pH. HA gel zymography revealed a single band corresponding to approximately 50 kDa. This study provided the first comprehensive view of the distribution of canonic HA-degrading proteins (HYAL1 and HYAL2) in human skin employing IHF and IHC. Furthermore, contrary to previous assumptions TMEM2, a novel hyaluronidase, as well as CEMIP, a protein involved in HA degradation, were localized in the human epidermis, as well as in the dermis.
Keywords: Proteins; Hyaluronoglucosaminidase; kůže; hyaluronoglukosaminidasa; Extracellular Matrix; hyaluronidase; Humans; hyaluronan; extracelulární matrix; Hyaluronic Acid; lidé; proteiny; CEMIP; TMEM2; skin; degradation; Skin; kyselina hyaluronová